Peremajaan Kawasan Kampung Bandeng Tambakrejo Semarang berdasarkan Preferensi Kelompok Usaha Masyarakat - Yuwananabdha Syahbi Syagata; Rina Kurniati (Ruang, 2019)
Kampung Bandeng Tambakrejo used to be the center of the middle-class milkfish industry, it is unfortunate that currently the area is experiencing a decline in quality both physically and activity. The production process of Bandeng village is very disturbed by inadequate physical and natural conditions, so that only a few business groups have survived to develop the milkfish business. The sustainability goal of the bandeng village is to conduct a research in the form of rejuvenation direction for Tambakrejo Bandeng village based on community business group preferences. The research method used in this study is qualitative research. Data collection is done by using interviews with resource persons, observation and documentation. The data in this study were obtained through interviews with determined resource persons or purposive sampling to bandeng group members as well as those who were active in the production of milkfish and shrimp processing and village elders who were aware of village growth and physical and non-physical sustainability of milkfish village rejuvenation directions based on Permen PU No. 02 / PRT / M / 2016 about improving the quality of slums and slums. The results of the study prove that there are physical identifications in the form of buildings, environmental roads, drainage, clean water, waste water, solid waste, and fire safety as well as non-physical aspects in Bandeng villages, namely production activities, trade services and social activities that support village activities. analyzed in the form of regional rejuvenation zones based on the preferences of community business groups. The direction of the rejuvenation of the milkfish village can be an approach to the community and the government in the form of rejuvenation from the community of the bandeng Tambakrejo village to refer to the government. The zoning forms are 5 zones that will be rejuvenated, namely there are settlement zones that accommodate the people affected by regional rejuvenation, trade zones and services found on secondary arterial roads, production and education zones in accordance with people's preferences located on the Tanggungrejo Raya road, and the Open Space Zone public in order to increase social development in increasing community social activities.